Development and impact of fuel economy standards and labels for light duty vehicles in Iran / Mostafa Mohammadnejad - Mostafa, Mohammadnejad (2012)
It was five years ago that Iranian government implemented various policies and programs such as applying quote on petrol consumption and changing the policies of subsidizing of petrol for optimization of fuel consumption in the transportation sector. At this time more than 58.4% of the total amount of oil products is consumed in the transportation section. The light duty vehicles consume around 56.5% of the fuel in transportation sector in Iran. Fuel saving initiatives such as the fuel economy standards and labels program for motor vehicles in transportation section has been applied in many developed countries around the world. In This study all the efforts are putted to grow a fuel economy standards program according to survey data from motor vehicles in transportation sector in Iran. A fuel economy label for Iranian cars is also built up to make sure that consumers are conscious concerning the fuel consumption of motor vehicles and will facilitate for easier evaluation among automobiles. And as a foundation of the fuel economy standards programs, a test procedure is chosen from present procedures to measure motor vehicles fuel consumption especially for motor vehicles which are locally produced. This research has also investigated the influence of executing the fuel economy standards and labels program from the perception of the fuel savings, economic savings and in addition the influence on the environment. The number of light duty vehicles in Iran has swiftly increased from approximately 3 million in 1998 to 8.7 million in 2008. Because of this growing quantity of motor vehicles in the country, lots of profit will come for the society as well as the environment by implementing of the fuel economy standards and labels program. By execution of the program around 23.9 billion liters of fuel is expected to be saved from 2013 to 2018. This means savings about 167,781 billion Rials in the bill and decrease of approximately 46.2 million tons of carbon dioxide emission.